Climate change contributions to conflict: an analysis of Syria, Yemen and Egypt - Harmon, Daniel, author; Harris, Peter, advisor; Stevis, Dimitris, committee member; Lindsay, James, committee member (Colorado State University. Libraries, 2021)
Ascriptions of false, causal connections between climate change and conflict sets a dangerous precedent for future refugee migration. Classification of refugees fleeing murderous regimes and/or circumstances, as climate migrants attempting to escape areas impacted climatically, reduces the subjective severity of the actual situations they were fleeing. Potential harmful ramifications to their asylum claims could result, consequential of a reduction in perceived threat to those migrants' lives by Consular officials. It also delegitimizes future climate refugees' asylum claims, those truly fleeing areas devastated by the effects of climate change/variability. Responsible consideration of the latest 2018 IPCC Special Report indicates, absent aggressive greenhouse gas (GHG) abatement measures, these are migrant circumstances that are increasingly likely to manifest. Such false assertions also detract from placing responsibility for the deaths of hundreds of thousands and the displacement of millions where it should be placed: with the Syrian, Yemeni and Egyptian governments. Affirming climate change as the main causal factor that initiated the Syrian conflict allows the regime to shift focus from its own administrative failures that were in fact the largest contribution to a conflict that has witnessed the deaths of hundreds of thousands. Similarly, false attribution of climate effects to Yemen's calamitous situation allows the worst humanitarian crisis in the world, involving famine conditions for millions of Yemenis, to be mistakenly viewed within an environmental context. Deaths and atrocities purportedly resulting from climate phenomena shift responsibility from where it should lay, with the Yemeni conflict's belligerents and their egregious actions. Also, the identification of Egypt's socio and political maladies as primarily consequent of climatic events disallows for the reckoning of the true causes that fomented rebellion during Egypt's Arab Spring "awakening." Finally, such false proclamations inhibit accurate advances to empirical knowledge that could be used in the future towards conflict mitigation and prevention. Implications for future climate refugees and those fleeing violent conflict demand accurate identification of conflict causation. To demand anything less as a member of a global citizenry is a dereliction of one's responsibility to humanity.